Analisis sistem pengendalian internal prosedur pengeluaran kas: COSO ICIF 2013 : Studi pada perusahaan konsultan pertambangan migas di Yogyakarta - Zahara, Inna; Sumayyah; Mubarrok, Zennul; Syah, Muhammad Erwan (Universitas Widya Mataram, 2024)
Financial management plays a crucial role in the survival and growth of companies. Cash disbursement is a common transaction in companies, necessitating effective internal control systems to prevent fraud or misappropriation. This study aims to analyze the internal control system and evaluate the internal control system over cash disbursements at PT WE, a mining consulting company in Yogyakarta. The research method used is descriptive-evaluative with a qualitative approach. Data were collected through direct observation and interviews with relevant staff. Evaluation was conducted based on the 17 principles within the five main components of the COSO Internal Control—Integrated Framework 2013. The results indicate that PT WE has implemented some internal control principles effectively, but there are still weaknesses in interdepartmental coordination, risk identification, and cash disbursement procedures. Based on the findings, it is recommended that PT WE improve coordination and communication between departments, systematically identify risks, and enhance cash disbursement procedures by establishing clear protocols, segregating related tasks, and periodically evaluating the internal control system.